Diffusion limited synthesis of wafer-scale covalent organic framework films for adaptative visual device - Minghui Liu; Junhua Kuang; Xiaocang Han; Youxing Liu; Wenqiang Gao; Shengcong Shang; Xinyu Wang; Jiaxin Hong; Bo Guan; Xiaoxu Zhao; Yunlong Guo; Jichen Dong; et al. (Nature Communications)
Abstract Synthesizing high-crystalline covalent organic framework films is highly desired to advance their applications in two-dimensional optoelectronics, but it remains a great challenge. Here, we report a diffusion-limited synthesis strategy for wafer-scale uniform covalent organic framework films, in which pre-deposited 4,4′,4″,4‴-(1,3,6,8-Tetrakis(4-aminophenyl) pyrene is encapsulated on substrate surface with a layer of covalent organic framework prepolymer. The polymer not only prevents the dissolution of precursor, but limits the reaction with terephthalaldehyde dissolved in solution, thereby regulating the polymerization process. The size depends on growth substrates, and 4-inch films have been synthesized on silicon chips. Their structure, thickness, patterning and crystallization degree can be controlled by adjusting building blocks and polymerization chemistries, and molybdenum disulfide have been used as substrates to construct vertical heterostructure. The measurements reveal that using covalent organic framework as a photosensitive layer, the heterojunction displays enhanced photoelectric performance, which can be used to simulate the adaptative function of visual system.